1998
DOI: 10.1161/01.res.83.7.738
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Human Fetal Cardiac Myocytes by a Human Immunodeficiency Virus-1–Derived Vector

Abstract: Cardiomyopathy associated with HIV-1 infection is a well-recognized complication. However, it is unknown whether direct cardiomyocyte infection is involved in the pathogenesis of the cardiomyopathy. An HIV-1-based lentiviral vector and wild-type HIV-1 were used to infect human fetal cardiac myocytes in a primary culture. Quantitative polymerase chain reaction, viral p24 antigen determination, and immunofluorescence were used to detect the synthesis of HIV-1 DNA and proteins after the infection. High-efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…These studies, which used highly sensitive in situ hybridization or PCR techniques, lack the requisite specificity to identify whether virus is present in myocytes or inflammatory cells for which these viruses are known to be tropic. In support of the notion that the virus is not resident within the cardiac myocytes is the observations of Robedollo et al, 24 who showed that HIV is incapable of infecting human neonatal cardiocytes. We did not perform in situ studies to detect SIV nucleic acid sequences in the present study because of the lack of specificity of the technique to localize the virus to cardiac myocytes or cells which express the CD4ϩ receptor.…”
Section: Discussionmentioning
confidence: 81%
“…These studies, which used highly sensitive in situ hybridization or PCR techniques, lack the requisite specificity to identify whether virus is present in myocytes or inflammatory cells for which these viruses are known to be tropic. In support of the notion that the virus is not resident within the cardiac myocytes is the observations of Robedollo et al, 24 who showed that HIV is incapable of infecting human neonatal cardiocytes. We did not perform in situ studies to detect SIV nucleic acid sequences in the present study because of the lack of specificity of the technique to localize the virus to cardiac myocytes or cells which express the CD4ϩ receptor.…”
Section: Discussionmentioning
confidence: 81%
“…3,[5][6][7]10,11,14 The etiology of the inflammatory response in this condition is poorly understood. The presence of HIV-infected cells within the myocardium of some HIV-infected individuals has repeatedly been documented, 3,[15][16][17][18][19] but the ability of HIV to infect cardiomyocytes remains controversial, 12,[20][21][22] as is the potential relationship of intramyocardial HIV-infected cells to the development of cardiac pathology. [12][13][14][15]17 Other opportunistic and general cardiotropic pathogens are identified with variable frequency, in most instances accounting for a minority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Whether HIV-1 and SIV can infect cardiomyocytes is still controversial [36], [37], whereas the fact that ALV has strong tropism for cardiomyocytes and Purkinje fibers is evidenced by the frequent formation of matrix inclusion bodies in these cells [27]–[29]. Despite these different degrees of tropism for cardiomyocytes, ALV-induced myocardial alteration is considered to be useful for clarifying the pathogenesis of retroviral cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%